Prime-Boost Vaccination with SA-4-1BBL Costimulatory Molecule and Survivin Eradicates Lung Carcinoma in CD8+ T and NK Cell Dependent Manner - Srivastava, Abhishek K.; Sharma, Rajesh K.; Yolcu, Esma S.; Ulker, Vahap; MacLeod, Kathryn; Dinc, Gunes; Shirwan, Haval (PLOS ONE, 2012)
Subunit vaccines containing universal tumor associated antigens (TAAs) present an attractive treatment modality for cancer primarily due to their safety and potential to generate long-term immunological responses that can safeguard against recurrences. However, TAA-based subunit vaccines require potent adjuvants for therapeutic efficacy. Using a novel form of the 4-1BBL costimulatory molecule, SA-4-1BBL, as the adjuvant of choice, we previously demonstrated that a single vaccination with survivin (SVN) as a bona fide self TAA was effective in eradicating weakly immunogenic 3LL tumors in >70% of C57BL/6 mice. The present study was designed to i) assess the therapeutic efficacy of a prime-boost vaccination and ii) investigate the mechanistic basis of vaccine efficacy. Our data shows that a prime-boost vaccination strategy was effective in eradicating 3LL lung carcinoma in 100% of mice. The vaccine efficacy was correlated with increased percentages of CD8+ T cells expressing IFN-γ as well as potent killing responses of both CD8+ T and NK cells in the absence of detectable antibodies to ssDNA as a sign of autoimmunity. Antibody depletion of CD8+ T cells one day before vaccination completely abrogated therapeutic efficacy, whereas depletion of CD4+ T cells had no effect. Importantly, NK cell depletion had a moderate (∼50% reduction), but significant (p<0.05) effect on vaccine efficacy. Taken together, these results shed light on the mechanistic basis of the SA-4-1BBL/SVN subunit vaccine formulation in a lung carcinoma model and demonstrate the robust therapeutic efficacy of the prime-boost immunization strategy with important clinical implications.